ANTIDIARRHOEAL AND IN VITRO ANTIBACTERIAL ACTIVITIES OF LEAVES EXTRACTS OF HIBISCUS ASPER. HOOK. F. (MALVACEAE). - G, ATEUFACK; W, NANA YOUSSEU; BR, DONGMO FEUDJIO; SAMA L, FONKENG; JR, KUIATE; A, KAMANYI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To evaluate the antidiarrhoeal and antibacterial activities of aqueous and methanolic leaves extracts of Hibiscus asper. Materials and Methods: The effect of aqueous and methanolic extracts of Hibiscus asper was assessing on the in vitro growth of 06 reference bacteria strains and 02 clinical isolates by determining the minimum inhibitory and bactericidal concentrations, using broth microdilution method as well as on the Shigella flexneri induced infectious diarrhoea, castor oil induced secretory diarrhoea and magnesium sulphate induced osmotic diarrhoea models in rats. Results: The methanolic extract was the most active, it inhibited the in vitro growth of 05 reference Gram (-) bacteria strains (Escherichia coli ATCC 11775, Escherichia coli ATCC 8789, Escherichia coli ATCC 10536, Enterobacter aerogenes ATCC 13048 and Salmonella typhi ATCC 6539) and one clinical isolate (Shigella flexneri). The MICs values were between 512 and 1024 Î¼g/ml.Â  In vivo, methanolic and aqueous extracts, administered at the same dose (500 mg/kg) caused a significant decrease (p<0.05) in the bacteria load in the faeces of rats, 08 and 12 days of treatment respectively. The methanolic extract was the most active, it reduced bacteria load within a shorter duration of treatment (08 days). The results of this study indicate that the methanolic and aqueous extracts of leaves of Hibiscus asper after 06 hours of observation, significantly inhibited (p<0.05; p<0.001) in vivo, diarrhoea induced experimentally by castor oil and magnesium sulphate, such as extending the latency, reducing the water content of faeces, the frequency of defecation and the number of wet defecations, compared to the negative control and to the dose 2.5 mg/kg of loperamide used as reference substance. Conclusion: We can therefore conclude that the leaves of Hibiscus asper possess antibacterial and antidiarrhoeal effects, resulting from their activity leading to the antibiotic mechanisms, the reabsorption of electrolytes (Na+, K+ and Cl-) and water. These results reconcile the ethnopharmacological use of Hibiscus asper in the treatment of gastro-intestinal infections. Key words: Antidiarrhoeal, Antibacterial, Hibiscus asper.